2015
DOI: 10.1016/j.freeradbiomed.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma F2-isoprostane class VI isomers at 12–18 weeks of pregnancy are associated with later occurrence of preeclampsia

Abstract: Preeclampsia (PE) has long been associated with early oxidative stress whereas the symptoms occur later in pregnancy. We have hypothesized that the oxidative stress in PE, as characterized by the presence of F 2 -isoprostanes (F 2 -isoPs) isomers in late pregnancy, should already be present in plasma at the first regular visit of the obstetrical follow-up. There are 64 possible isomers of F 2 -isoPs derived from the oxidation of arachidonic acid (AA) but only one of these isomers has been investigated so far i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Lupus shares this feature as the key mechanism underlying hypertension, renal dysfunction, and other organ injury [29]. Indeed, the endothelial dysfunction in both preeclampsia and lupus have also been shown to be due, at least in part, to excessive oxidative stress secondary to NOX activation [12,30,31]. Recently, in murine models of lupus, hydroxychloroquine was shown to reverse endothelial dysfunction via the downregulation of NOX, and subsequently, oxidative stress [24,32].…”
Section: Discussionmentioning
confidence: 99%
“…Lupus shares this feature as the key mechanism underlying hypertension, renal dysfunction, and other organ injury [29]. Indeed, the endothelial dysfunction in both preeclampsia and lupus have also been shown to be due, at least in part, to excessive oxidative stress secondary to NOX activation [12,30,31]. Recently, in murine models of lupus, hydroxychloroquine was shown to reverse endothelial dysfunction via the downregulation of NOX, and subsequently, oxidative stress [24,32].…”
Section: Discussionmentioning
confidence: 99%
“…The number in the affected and control groups represents the number of people tested. Data for this figure was extracted from references [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109], [110], [111], [112], [113], [114], [115], [116], [117], [118], …”
Section: Figmentioning
confidence: 99%
“…26 This endothelial dysfunction may be due to excessive oxidative stress that occurs secondary to nicotinamide adenine dinucleotide phosphate oxidase (NOX) activation. 2729 Recently, a study using a mouse model has shown that HCQ can protect against oxidative stress-induced endothelial dysfunction and thereby improve renal function inhibiting NOX activity in SLE. 30,31 In vitro studies have shown that HCQ mitigated TNF-α-induced human umbilical vein endothelial cell production of 8-isoprostane and NOX expression.…”
Section: Discussionmentioning
confidence: 99%